CSF or middle ear effusion? Diagnostical dilemmas in a patient with temporal bone meningioma: A case report - Glen J.F. Kemps; Douwe de Boer; Maud P.M. Tijssen; Dirk H.P.M. Kunst; Jérôme J. Waterval (Heliyon, 2024)
Introduction: Cerebrospinal fluid (CSF) fistulas are a rare phenomenon, that can lead to life-threatening complications if left untreated. Presenting as rhinorrhea or otorrhea, they can be difficult to diagnose due to admixture of other bodily fluids. Typically, CSF fistulas develop after trauma, but in rare instances, they can be diagnosed in patients with a neoplastic lesion. Objective: To discuss several steps in diagnosing CSF fistulas. Patient: A fifty-year-old female with an intra-osseous temporal bone meningioma. Interventions: For diagnosing CSF admixture in fluids, two tests are looked into: beta-2 transferrin (β2T) and beta-trace protein (βTP) testing. Conclusion: Testing for βTP is a highly sensitive, quick and non-invasive method to assess CSF admixture in middle ear effusion. Because of its lower cost, faster results and easy sample collection, βTP testing has in our clinic replaced β2T testing. The current case illustrates a rare etiology of a CSF fistula, where β2T testing presumably showed false-negative results and βTP testing showed true-positive results.